The impact of gender imbalances in political representation in Zimbabwe: a case of Gweru urban constituency since 1980-2013 - Mafuta, Knowledge (Midlands State University, 2015)
This research was an analysis of gender imbalances in political representation in Zimbabwe in the context of Gweru Urban Constituency since 1980-2013. A review of the causes and factors that militates against women political representation was discussed. Also the reasons why women should be politically represented and the legal and structural policies promoting women political representation was also discuss. Theories were the support base of the thesis. Both qualitative and quantitative research methods were used to gather information with the use secondary and primary sources. The researcher made use of questionnaires and interviews in gathering data from a selected population sample. The target population comprised of the permanent residence of Gweru urban but only those of the voting majority, as well as male and female councillors and lobby groups. About 60 questionnaires were administered. The researcher were necessary had to use the native language thus shone to assist in the interpretation of questions. The data gathered from the field was presented by the use of tables, bar graphs and pie-charts. The researcher had to analyse the data he got and summarised. The data gathered shows that women were militated by political, social, economic and legal factors. As a result the researcher had to give recommendations on what has to be done to redress gender imbalances in political representation.